What's Next? Lessons on Education Recovery : Findings from a Survey of Ministries of Education amid the COVID-19 Pandemic - UNESCO; UNICEF; World Bank; OECD (UNESCO, Paris, UNICEF, New York, World Bank, Washington, DC, and OECD, Paris, 2021)
United Nations Educational, Scientific and Cultural Organization (UNESCO), the United Nations Children’s Fund (UNICEF), the World Bank and the Organisation for Economic Co-operation and Development (OECD) have collaborated in the third round of the Survey on National Education Responses to COVID-19 (coronavirus) School Closures, administered by the UNESCO Institute for Statistics (UIS) and OECD to Ministry of Education officials. The questions covered four levels of education: pre-primary, primary, lower secondary and upper secondary. While the first two rounds of the survey were implemented during the periods May-June and July-October 2020, respectively, the third round was implemented during the period February-June 2021. In total, 143 countries responded to the questionnaire. Thirty-one countries submitted responses to the OECD ("OECD survey") and 112 countries responded to the UIS ("UIS survey"). Seven countries responded to both surveys. In these instances, the more complete set responses were used in analysis.